Flexbar 3.0: SIMD and multicore parallelization - Roehr, Johannes; Dieterich, Christoph; Reinert, Knut (Bioinformatics, 2017)
AbstractMotivation. High-throughput sequencing machines can process many samples in a single run. For Illumina systems, sequencing reads are barcoded with an a